1982
DOI: 10.1111/j.1365-2125.1982.tb01992.x
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril maleate and a lysine analogue (MK‐521) in normal volunteers; relationship between plasma drug levels and the renin angiotensin system.

Abstract: 1 Two single doses of 10 mg each of the converting enzyme inhibitor enalapril maleate or MK-421 and of its lysine analogue (MK-521) were administered p.o. to twelve male volunteers. 2 The active diacid metabolite of MK421 and the lysine analogue were determined by radioimmunoassay and MK-421 by the active metabolite method following in vitro hydrolysis. 3 Peak serum levels of MK-421, active metabolite and lysine analogue were reached within 1, 3 to 4, and 6 h respectively. Practically all MK-421 had disappeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(37 citation statements)
references
References 11 publications
1
36
0
Order By: Relevance
“…The time course of MK-422 and MK-521 in serum closely paralleled their pharmacological and biochemical effects (Biollaz et al, 1982). In addition to the results of Biollaz et al (1982), Swanson et al (1981) reported an inverse relationship between plasma converting enzyme activity and the serum concentration of MK-422 in subjects who had received enalapril maleate.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The time course of MK-422 and MK-521 in serum closely paralleled their pharmacological and biochemical effects (Biollaz et al, 1982). In addition to the results of Biollaz et al (1982), Swanson et al (1981) reported an inverse relationship between plasma converting enzyme activity and the serum concentration of MK-422 in subjects who had received enalapril maleate.…”
Section: Discussionmentioning
confidence: 64%
“…This level of inhibition occurred about 1 h after enalapril maleate administration and about 2 h after MK-521 (Biollaz et al, 1982). From the serum concentration versus time profiles (Figures 2 and 3), the corresponding inhibitor concentrations were 20 and 18 nm.…”
Section: Discussionmentioning
confidence: 91%
“…6 - 10 Although this is likely to reflect the wide range of intersubject variability in pharmacokinetic responses, particularly when group data are evaluated, there is preliminary evidence that concentration-effect relations for ACE inhibitors can be more readily identified when individual subjects are considered.…”
mentioning
confidence: 99%
“…With most compounds, the components of the renin-angiotensin system (RAS) including ACE activity, angiotensin I and II and plasma renin activity have been determined before and during ACE inhibition. Whenever possible, these biochemical determinations have been correlated with measured plasma drug concentrations to establish a concentration-effect relationship (Biollaz et al, 1982;Bussien et al, 1985;Nussberger et al, 1987). The in vitro measurement of plasma ACE activity appeared to be a useful means to determine the degree of RAS blockade and has been used extensively for the purpose of characterizing pharmacokinetics although evidence is accumulating which suggests that it is not necessary to suppress ACE activity permanently to decrease blood pressure (Boomsma et al, 1981;Waeber et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to characterize better the in vivo inhibition of ACE, we have calculated in the past several years the ratio of angiotensin II to angiotensin I measured in plasma (Biollaz et al, 1982). This parameter should actually reflect not only the enzymatic activity taking place in the plasma but also the conversion occurring in endothelial cells.…”
Section: Introductionmentioning
confidence: 99%